2015
DOI: 10.1007/s00268-015-3378-9
|View full text |Cite
|
Sign up to set email alerts
|

Intrapleural Fibrinolytic Therapy for Residual Coagulated Hemothorax After Lung Surgery

Abstract: Intrapleural fibrinolytic agents should be considered a useful therapeutic option for the treatment of postoperative residual hemothorax. This method appears to be safe and effective in >90 % of patients with postoperative hemothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In recent years, the use of a tissue plasminogen activator (tPA) such as urokinase, which liquefies the clotted hemothorax, has come up as a less invasive method for treatment (8). Fibrinolytic agents as streptokinase or urokinase have been used safely in the posttraumatic hemothorax setting (9) or after lung resections (10). The risk of relevant bleeding using these agents is described in the literature with 2-15% in mostly immunocompetent patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of a tissue plasminogen activator (tPA) such as urokinase, which liquefies the clotted hemothorax, has come up as a less invasive method for treatment (8). Fibrinolytic agents as streptokinase or urokinase have been used safely in the posttraumatic hemothorax setting (9) or after lung resections (10). The risk of relevant bleeding using these agents is described in the literature with 2-15% in mostly immunocompetent patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it can dissolve the cellulose deposited on the pulmonary surface, which makes pulmonary reexpansion possible. Because this method is simple and provides a way of treating patients without great economic burden or special equipment, it deserves broader application [1]. In the present study, 61 patients were eligible for thoracic puncture and chest tube drainage.…”
Section: The Treatment Of Thoracic Trauma Combined With Atelectasismentioning
confidence: 99%
“…1,9,14,21 Fibrinolytic agents, such as streptokinase and urokinase, convert plasminogen to plasmin, which breaks down fibrin within clot and adhesions. Theoretically, the dissolution of clot and loculations should improve evacuation of retained collections, [23][24][25] but in the 2012 AAST trial, of the 15 patients initially treated with IPFT, 10 (67%) required a second procedure. 9 Conversely, Kimbrell and colleagues successfully treated 23/25 (92%) RH that were at least 300 mL on CT with IPFT 21 and other small studies have shown similar success in management of RH with IPFT.…”
Section: Intra-pleural Fibrinolytic Therapymentioning
confidence: 99%
“…27,28 Although not dealing specifically with traumatic RH, IPFT effectively treated 91.3% of 46 patients with sizable RH (>1/3 of the hemithorax) after elective lung surgery, with an average of 6.2 days between the original surgery and IPFT initiation. 23 While the literature has yet to adequately characterize the ideal IPFT group, perhaps those with low volume RH or who could not tolerate an operation would be good candidates for IPFT. Such a group could also still result in cost savings, despite the cost of the fibrinolytics.…”
Section: Intra-pleural Fibrinolytic Therapymentioning
confidence: 99%